Pengembangan Multimedia Interaktif Berbasis Articulate Storyline pada Pembelajaran Biologi Materi Sistem Reproduksi Kelas XI/F di SMAN 1 Kec. Lareh Sago Halaban - Jefysa, Indah; Fitri, Dwi Rini Kurnia (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Educators have not widely recognized interactive multimedia, and students show limited interest in the interactive multimedia already provided by educators. This lack of engagement leads to boredom and a decline in students’ enthusiasm for learning biology. The problem statement of this study focuses on the validity and practicality of interactive multimedia based on Articulate storyline. The objective of this research is to determine the results of the validity and practicality of the Articulate storyline-based interactive multimedia. This study employs a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, and Disseminate), although it is limited to the Develop stage. Product validation was conducted by three validators, consisting of two lecturers and one biology teacher. The product trial was carried out by one biology teacher and 35 students. The instruments used in this study include a validity assessment sheet and a practicality assessment sheet. Data analysis was performed using descriptive quantitative methods. The findings indicate that the Articulate storyline-based interactive multimedia was categorized as highly valid, with a percentage of 83.03%. The practicality results also showed that the multimedia was highly practical, with a percentage of 87.84% based on student questionnaires and 93.83% based on educator questionnaires. Therefore, it can be concluded that the development of interactive multimedia based on Articulate storyline can enhance students’ motivation and interest in learning biology.